The management financial and competitive strategy: analysis of their differences according to business size (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of this document was to empirically determine the existence of significant differences between the size of the companies according to the use of their financial management and their competitive strategy. A survey was used in 78 SMEs of the commerce sector in general, in the Municipal and Industrial delegations of the Central municipality of the state of Tabasco, for this purpose the methodology used is non-experimental, cross-sectional, descriptive and with a quantitative approach. The data was studied through inferential statistics, with a one-factor ANOVA test, whose empirical results show that there are significant differences in financial management and competitive strategy with the size of the company, large businesses have a higher level of financial management, greater application of competitive strategies than medium, small and micro companies.
Keywords: financial management; management; company size; strategy; economic competition